2020
DOI: 10.1136/bmjopen-2019-035672
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of a supplement combination for hand osteoarthritis pain: protocol for an internet-based randomised placebo-controlled trial (The RADIANT study)

Abstract: IntroductionHand osteoarthritis (HOA) is a highly prevalent disabling joint disease. The current management regimens are limited. Potentially as a consequence, many people turn to complementary and alternative medicines for symptomatic relief. A combination of two or more supplements is common in clinical practice; however, evidence for the efficacy of this approach is lacking. The aim of this study is to investigate the efficacy of a supplement combination for treating symptomatic HOA in comparison to placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 47 publications
(51 reference statements)
0
12
0
1
Order By: Relevance
“…Thirty‐five trials reported durations that ranged from 1 month to 13 years (median 11 mo). The lead investigators of over half (30) of the trials were based in North America, 18–47 11 were in the UK, 48–58 3 in other European countries 59–61 and 1 in Australia 62 . Most trials (40) included participants only in the country of the lead investigator; however, 4 trials included participants in 2 countries, 33,39,46,50 and 1 reported participants in more than 2 countries (11 countries, 5 continents) 24 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty‐five trials reported durations that ranged from 1 month to 13 years (median 11 mo). The lead investigators of over half (30) of the trials were based in North America, 18–47 11 were in the UK, 48–58 3 in other European countries 59–61 and 1 in Australia 62 . Most trials (40) included participants only in the country of the lead investigator; however, 4 trials included participants in 2 countries, 33,39,46,50 and 1 reported participants in more than 2 countries (11 countries, 5 continents) 24 …”
Section: Resultsmentioning
confidence: 99%
“…12 tested dietary supplements 19,21,[27][28][29]32,34,49,[58][59][60]62 or herbal medicines; 6 tested licensed medicines for new or extended indications [43][44][45][46]52,55 ; and 6 tested not yet licensed medicines. 20,26,30,38,56,61 Of the remainder, there were 3 device trials, [40][41][42] 3 screening trials 36,37,51 and 1 trial testing a methodological intervention (remote set-up of mobile health technology for a longitudinal cohort study).…”
Section: Description Of Included Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioavailability of curcumin is a major challenge because it is inherently low in humans, but new formulations have enhanced the therapeutic efficacy of curcumin [ 142 , 143 ]. Furthermore, the use of curcumin in combination with other natural products, such as Boswellia serrate , gingerly, and pipeline, are being studied in several clinical trials to investigate whether their therapeutically synergy enhances their performance in OA treatment but the results showed no significant difference between each component separately or in combination [ 144 , 145 , 146 ].…”
Section: Natural-compound-based Treatments For Oa Therapymentioning
confidence: 99%
“…Отмечалось 34 несерьезных нежелательных явления в группе комбинированной терапии (кожные реакции и обострения боли, связанные с физической нагрузкой). Позже этот же авторский коллектив в РКИ RADIANT показал отсутствие эффекта от приема пищевых растительных добавок на симптомы ОА кистей [35][36][37].…”
Section: преимущества топических нпвп содержащих диклофенакunclassified